Association of Nonrecovery of Kidney Function After Pediatric Acute Kidney Injury With 5-Year Kidney and Nonkidney Outcomes. (18th January 2022) - Ulrich, Emma H.; Hessey, Erin; Perreault, Sylvie; Dorais, Marc; Jouvet, Philippe; Phan, Veronique; Zappitelli, Michael
Abstract : Supplemental Digital Content is available in the text. Abstract : IMPORTANCE: Acute kidney injury is common in critically ill children, but the long-term outcomes are not well defined. OBJECTIVES: Evaluated whether nonrecovery of kidney function, following acute kidney injury, was associated with postdischarge mortality, healthcare utilization, and chronic kidney disease. DESIGN: Retrospective, two-center, observational study. SETTING: Two ICUs at tertiary children's hospitals in Montreal, QC. PARTICIPANTS: Pediatric patients (age ≤ 18 yr) with index admission to intensive care between January 1, 2003, and March 31, 2005. Children were excluded if they 1) died during admission, 2) did not have serum creatinine or urine output measured, 3) did not develop acute kidney injury, 4) could not be linked to administrative health data, and 5) (for chronic kidney disease outcome) had pre-existing renal disease by chart review, baseline estimated glomerular filtration rate measurement, or administrative health data codes. MAIN OUTCOMES AND MEASURES: Three-hundred seventy-eight patients' data were included for long-term mortality and healthcare utilization outcomes; 316 patients for long-term chronic kidney disease outcome. Outcomes were defined using provincial administrative healthcare data diagnosis, procedure, and billing codes. MAIN RESULTS: Nonrecovery of kidney function, defined as serum creatinine greater than or equal to 1.5× baseline at ICU discharge, occurred in 51 patients (13%). Nonrecovery of kidney function was not associated with long-term mortality (at 5–7 yr following hospital discharge), increased hospitalizations or emergency department visits (at 30-days, 1-year, and 5-yr follow-up), or increased physician visits (at 1- and 5-yr follow-up). Nonrecovery was associated with increased 30-day physician visits (adjusted relative risk, 1.40; 95% CI, 1.13–1.73) and chronic kidney disease diagnosis within 5 years of discharge (adjusted hazard ratio, 4.92, 95% CI, 1.77–13.70). CONCLUSIONS AND RELEVANCE: Nonrecovery of kidney function following an episode of acute kidney injury in critically ill children is associated with nearly five-fold increased risk for long-term chronic kidney disease. Acute kidney injury nonrecovery may be a useful marker to identify patients that are particularly important to follow-up post discharge for chronic kidney disease detection.